An Sfi1p-Like Centrin-Binding Protein Mediates Centrin-Based Ca(2+)-Dependent Contractility in Paramecium tetraurelia - Gogendeau, Delphine (American Society for Microbiology (ASM), 2007)
The previous characterization and structural analyses of Sfi1p, a Saccharomyces cerevisiae centrin-binding protein essential for spindle pole body duplication, have suggested molecular models to account for centrin-mediated, Ca(2+)-dependent contractility processes (S. Li, A. M. Sandercock, P. Conduit, C. V. Robinson, R. L. Williams, and J. V. Kilmartin, J. Cell Biol. 173:867-877, 2006). Such processes can be analyzed by using Paramecium tetraurelia, which harbors a large Ca(2+)-dependent contractile cytoskeletal network, the infraciliary lattice (ICL). Previous biochemical and genetic studies have shown that the ICL is composed of diverse centrin isoforms and a high-molecular-mass centrin-associated protein, whose reduced size in the démaillé (dem1) mutant correlates with defective organization of the ICL. Using sequences derived from the high-molecular-mass protein to probe the Paramecium genome sequence, we characterized the PtCenBP1 gene, which encodes a 460-kDa protein. PtCenBP1p displays six almost perfect repeats of ca. 427 amino acids (aa) and harbors 89 potential centrin-binding sites with the consensus motif LLX(11)F/LX(2)WK/R, similar to the centrin-binding sites of ScSfi1p. The smaller (260-kDa) protein encoded by the dem1 mutant PtCenBP1 allele comprises only two repeats of 427 aa and 46 centrin-binding sites. By using RNA interference and green fluorescent protein fusion experiments, we showed that PtCenBP1p forms the backbone of the ICL and plays an essential role in its assembly and contractility. This study provides the first in vivo demonstration of the role of Sfi1p-like proteins in centrin-mediated Ca(2+)-dependent contractile processes.